The Guidelines for Improving the Performances of the Administrators of the Educational Institutes under the Primary Educational Service Area Office Surin 2 - Saendee, Ponlawat; Sitthisuea, Thanyathep; Kakkaew, Vasanchai (Academic MCU Buriram Journal, 2023)
The purpose of this research were: 1) to study the performance levels of the administrators of the educational institutes under the Primary Educational Service Area Office Surin 2, 2) to study the guidelines for improving the performances of the administrators of the educational institutes under the Primary Educational Service Area Office Surin 2, and 3) to evaluate the guidelines for improving the performances of the administrators of the educational institutes under the Primary Educational Service Area Office Surin 2. The population is 2,005 according to Craigsie and Morgan’s chart. The population and samples included 322 administrators and teachers. The research tool is a questionnaire with a confidence value of 0.982, an in-depth interview and a guideline assessment. The statistics used in the analysis were frequency distribution, percentage values, mean and standard deviation. The research results found that: 1. By studying the performance levels of the administrators of the educational institutes under the Primary Educational Service Area Office Surin 2, it was found that the overall performance level of the administrators of the educational institutes under the Primary Educational Service Area Office Surin 2 was high. 2. By studying the guidelines for improving the performances of the administrators of the educational institutes under the Primary Educational Service Area Office Surin 2, the results from studying the performances of the administrators were synthesized by the researcher and drafted with the results from the in-depth interviews with the experts. As a result, there were 17 drafted guidelines. 3. To evaluate the guidelines for improving the performances of the administrators of the educational institutes under the Primary Educational Service Area Office Surin 2; the appropriateness, possibilities and benefits were evaluated by the researcher. It was found that the overall level was the highest level.